2004
DOI: 10.4141/a03-048
|View full text |Cite
|
Sign up to set email alerts
|

Time of feeding and growth promotant effects on the winter growth performance and carcass traits of steers

Abstract: . 2004. Time of feeding and growth promotant effects on the winter growth performance and carcass traits of steers. Can. J. Anim. Sci. 84: 133-144. The effects of time of day of feeding and estrogenic growth promotant on growth performance and carcass traits were determined in three experiments conducted over 3 yr (winters 1998-1999, 1999-2000, 2000-2001). Crossbred steers (year 1, n = 144, year 2, n = 128, year 3, n = 144) were assigned at fall weaning on the basis of sire, age (190 ± 21 d, mean ± SD), and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
(39 reference statements)
2
13
1
Order By: Relevance
“…Previous studies either did not collect behaviour data Small et al 2004;Holt and Pritchard 2005) or did not examine differences in feeding behaviour during the day and night (SchwartzkopfGenswein et al 2004). Consequently, it was unclear whether provision of feed ad libitum during the evening would overcome the natural inclination of cattle to eat at dawn and dusk (Lefcourt and Adams 1999).…”
Section: Effect Of Time Of Feed Delivery On Feeding Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies either did not collect behaviour data Small et al 2004;Holt and Pritchard 2005) or did not examine differences in feeding behaviour during the day and night (SchwartzkopfGenswein et al 2004). Consequently, it was unclear whether provision of feed ad libitum during the evening would overcome the natural inclination of cattle to eat at dawn and dusk (Lefcourt and Adams 1999).…”
Section: Effect Of Time Of Feed Delivery On Feeding Behaviourmentioning
confidence: 99%
“…If this prevents cold acclimation, maintenance energy requirements will be reduced, thereby increasing growth rates and/or efficiency. Several studies have found that evening feeding increases growth rate and feed efficiency across the winter feeding period Schwartzkopf-Genswein et al 2004;Small et al 2004;Holt and Pritchard 2005). However, only one study has actually studied the thermoregulatory physiology of cattle fed in the morning vs. evening specifically during the coldest intervals of the winter feeding period (Bergen et al 2007), and none have examined feeding behaviour.…”
Section: Finishing Periodmentioning
confidence: 99%
“…Evening rather than morning feeding can improve the performance of beef cattle. [5][6][7][8] Ruminants have evolved to ruminate mostly overnight, when the rumen develops a greater fermentation capacity and volume, compared with daytime. 9 Feeding ruminants in the evening could thus significantly alter postfeeding fermentation patterns.…”
Section: Research Findingsmentioning
confidence: 99%
“…In so doing, rumen should possess differential capacities for bioprocessing of different substrates. In modern ruminant farming with no grazing, however, such natural patterns of rumen ecology are in ways interrupted or altered [6][7][8][9][10]. For instance, feed delivery could well be exercised during evening and night hours.…”
Section: Philosophy For Practicementioning
confidence: 99%